Case Study : Jer Groceries Sdn. Bhd. / Mohamad Nur Izuansyah Mat Nasir - Mat Nasir, Mohamad Nur Izuansyah (2021)
I have already decided to interview a young female entrepreneur who has already successfully run a grocery store business near my village. As in the picture I have shown, this woman is a very great woman because she has already managed to set up a grocery store in front of her house and it turns out that the busines she has been running for 10 years has benefited of her family. She was the owner of a grocery store who known as the JER grocery store. her full name is zanariah binti daud 36 years’ old, but she’s famouse known by the nickname kak jer. She was born in 1985 at Kampung Padang Mandol and raised by her mother and her father at the same village and untill now she still lives in the village of Kampung Padang Mandol and runs a grocery store business in the same village. She is the fourth child of 7 siblings. She has only another younger sister who is still studying at Sekolah Menengah Kebangsaan Chabang Empat Tumpat Kelantan. After finish spm, she once continued his studies at Politeknik Kok Lanas in engineering for 2 and a half years. After that, she has gained a lot of work experience, such as she has worked in a cake shop in Pasir Mas, worked in a factory in Selangor, worked in a supermarket, worked in a hotel as a food waiter and many more. She also used to work as a coach at the Paya Indah camp PLKN in selangor for 10 years and now she has quite due to certain factors. After the death of her father, she had decided to open a small grocery store in front of her house, by using her saving as capital and her business is thriving to this day, and now her grocery store business is growing and her stores are getting bigger. now her grocery store business is assisted by her 2 younger sister and broher and a few other employees.